Оrthoepy in the curricula for the lower grades of primary school - Мirjana M. Stakić (Inovacije u Nastavi, 2021)
We point out the importance of working on the correct articulation of sounds and analyze the representation of orthoepy in the curricular contents for the subject Serbian Language in the lower grades of primary school. The results of the content analysis show that the importance of a continuous work on the correct articulation of sounds has not been recognized in the new curricula. The work on the pronunciation of sounds is included only in the curriculum for the first grade. A comparative analysis of the old (2004, 2005, 2006) and new curricula (2017, 2018, 2019) has shown that the reform rejected all the contents that continuously extended the work on the pronunciation of sounds until the fourth grade. The state of the pronunciation norm in practice, confirmed by the research results, indicates numerous problems of atypical articulation that is not organic in nature. Therefore, the pedagogical implications are that the changes of and/or additions to the content of orthoepy related to the pronunciation of sounds should be included in the mother tongue curricula for the lower grades of primary school and made operational through outcomes as the functional knowledge of the pronunciation norm. These are the contents that were represented in the curricula before the reform, and they refer to the pronunciation of affricates (ч, ћ, џ, ђ) and fricatives (х) in the third and fourth grades. This would enable continuity in the work of the practitioners which is necessary to correct the mistakes in the pronunciation of sounds that are not organic in nature and to strengthen the correct articulation.